2014
DOI: 10.3892/mmr.2014.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Schisandra chinensis on acetaminophen-induced hepatotoxicity

Abstract: Abstract. Schisandra chinensis is a well-known traditional medicinal herb. Acetaminophen is a commonly used over-the-counter analgesic and overdose of acetaminophen was the most frequent cause of acute liver failure. However, no studies have demonstrated the role of Schisandra chinensis in acetaminophen-induced acute liver failure to the best of our knowledge. In this study, an acute liver injury model was established in mice using acetaminophen. The protective role of Schisandra chinensis was detected by hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…MAPKs, including ERK, JNK and p38, are part of the IGF-IR signaling pathway and convert extracellular stimuli into a wide range of cellular responses. These proteins serve important roles in cell proliferation, differentiation, metabolism, survival and death (87,88), as well as in oxidative damage (77,78). JNK is primarily involved apoptosis and is activated by oxidative damage, whereas ERK regulates cell growth and differentiation, is activated by oxidative damage, and acts as a cell death suppression signal to maintain homeostasis (89).…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs, including ERK, JNK and p38, are part of the IGF-IR signaling pathway and convert extracellular stimuli into a wide range of cellular responses. These proteins serve important roles in cell proliferation, differentiation, metabolism, survival and death (87,88), as well as in oxidative damage (77,78). JNK is primarily involved apoptosis and is activated by oxidative damage, whereas ERK regulates cell growth and differentiation, is activated by oxidative damage, and acts as a cell death suppression signal to maintain homeostasis (89).…”
Section: Discussionmentioning
confidence: 99%
“…Recently evidence has been accumulated that those side effects like nephrotoxicity and hepatotoxicity are closely related to the activity of reactive oxygen species (ROS) (Gurocak et al, 2013;Rodrigues et al, 2014;Wang et al, 2014). ROS including superoxide anion radical (O 2 ·-), hydroxyl radical (·OH), hydrogen peroxide (H 2 O 2 ), singlet oxygen ( 1 O 2 ) and nitric oxide (NO), which are directly involved in oxidative damage of cellular macromolecules such as lipids, proteins and nucleic acids in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that inhibition of c-Jun N-terminal kinase signaling pathway is involved in the liver protective effect of SCE in mice with acetaminophen-induced liver injury. 59 Moreover, SCE or its components can inhibit nuclear transcription factor-κB and mitogen-activated protein kinase signaling pathways, contributing to its beneficial effects. 80 , 83 , 84 Moreover, the RNA interfering efficiency may change, contributing to these varying effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous preclinical studies have found that SCE and its major active lignanoids protected the liver in various liver-injured models, with different mechanisms involved in its hepatoprotective activities. 43 59 These include antioxidation, inhibition of cytokine production, inhibition of apoptosis, activation of Nrf2, and other possible mechanisms. 51 59 However, the mechanism is not fully understood, and the role of Nrf2 in the hepatoprotection of SCE is not elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation